2000
DOI: 10.1161/01.str.31.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide and Cerebral Vasospasm in Subarachnoid Hemorrhage

Abstract: Background and Purpose-Hyponatremia has been shown in association with cerebral vasospasm (CVS) following aneurysmal subarachnoid hemorrhage (SAH). In the past few years there has been increasing evidence that brain natriuretic peptide (BNP) is responsible for natriuresis after SAH. The purpose of the present study was to investigate the relationship between BNP plasma concentrations and CVS after aneurysmal SAH. Methods-BNP plasma concentrations were assessed at 4 different time periods (1 to 3 days, 4 to 6 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…Results from these studies indicated that it was the clinically apparent brain ischemia, rather than the angiographic or transcranial Doppler defined vasospasm, that was associated with the BNP increase. 13,19,20 This finding was later supported by Taub et al, 22 who showed in a larger study that high levels of BNP were associated with cerebral infarction detected on CT images. Brain natriuretic peptide has also been explored as a marker of cardiac injury in SAH patients, and high BNP at admission as well as high troponin-I on the 3rd day after admission has been found to be associated with increased inpatient deaths.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Results from these studies indicated that it was the clinically apparent brain ischemia, rather than the angiographic or transcranial Doppler defined vasospasm, that was associated with the BNP increase. 13,19,20 This finding was later supported by Taub et al, 22 who showed in a larger study that high levels of BNP were associated with cerebral infarction detected on CT images. Brain natriuretic peptide has also been explored as a marker of cardiac injury in SAH patients, and high BNP at admission as well as high troponin-I on the 3rd day after admission has been found to be associated with increased inpatient deaths.…”
mentioning
confidence: 67%
“…Earlier studies have indicated that brain ischemia is associated with the increase of BNP. 13,19,20,22 Nakamura et al 15 described that BNP is higher in unconscious SAH patients than in awake patients. Brain ischemia appears several days after the bleeding as delayed ischemic neurological deficits, which could be associated with the BNP increase.…”
Section: Discussionmentioning
confidence: 99%
“…The study was a prospective, single-centre, observational, cohort study of consecutive patients admitted to a general intensive care unit (ICU). All patients admitted to ICU during the study period were included, except those with severe neurological injury, because B-type natriuretic peptide levels are raised in brain injury [14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is a natriuretic, effective vasodilator factor and it is able to decrease the cerebral blood flow as a result of its systemic effects (16,20,21). This neurohormone is secreted as preproBNP and then divided as N-Terminal proBNP and BNP by being enzymatically disrupted due to the stretching of ventricular myocytes.…”
Section: Akgun B Et Al: the Correlation Of Serum Nt-probnp Levelsmentioning
confidence: 99%